A 2D NiFe Bimetallic Metal–Organic Frameworks for Efficient Oxygen Evolution Electrocatalysis. Issue 1 (15th January 2019) - Hao, Yongchao; Liu, Qinglin; Zhou, Ying; Yuan, Zeqian; Fan, Yanan; Ke, Zhuofeng; Su, Cheng‐Yong; Li, Guangqin
Abstract : The oxygen evolution reaction (OER) is the cornerstone for many important energy conversion devices, including metal–air battery and water splitting. Herein, an optimized NiFe‐based metal–organic framework is developed as highly efficient active material for OER. It just needs a low overpotential of 0.31 V to deliver a current density of 10 mA cm −2 with a favorable Tafel slope of 43.7 mV dec −1 in 0.1 m KOH electrolyte for the as‐prepared Ni0.75 Fe0.25 BDC, which is superior to RuO2 . This efficient catalytic performance is due to the introduction of Fe in Ni‐based MOFs could benefit the kinetics and charge transfer efficiency, resulting in the optimal activity toward OER. Besides, the obtained active material demonstrates good stability, suggesting the great potential value in sustainable electrochemical energy storage and conversion devices. Abstract : A two‐dimensional Ni‐based MOF with Fe incorporated has been prepared for efficient oxygen evolution electrocatalysis. After optimizing the ratio of Ni and Fe, the Ni0.75 Fe0.25 BDC exhibited superior OER activity with an overpotential of 0.31 V and a Tafel slope of 47.4 mV dec −1 and stability.